International Society for the Advancement of Kinanthropometry (ISAK) Global: international accreditation scheme of the competent anthropometrist - Vladimir Schuindt da Silva; Maria Filomena Soares Vieira (Revista Brasileira de Cineantropometria e Desempenho Humano)
The anthropometric assessment of a person or population is used by professionals from different areas (health, sports, education, ergonomics, engineering), and the quality of the measures obtained by them determines the success of their interventions. This point of view aims to underline the importance of training these professionals through The International Anthropometry Accreditation Scheme (IAAS) implemented by The International Society for the Advancement of Kinanthropometry (ISAK), which aims to create and maintain an international network of professionals updated continuously from the practical and scientific point of view in the anthropometric measurement of excellence. We describe the four-level hierarchical structure of IAAS, which is guided by the rules defined in the ISAK Handbook and the anthropometric procedures described in the ISAK manuals, as well as the importance and functionality of the ISAK website. It is suggested that an ISAK mobile app be developed to, among other things, facilitate communication among its members, streamline data management of accreditation courses and increase the organization’s international projection.